Cabardites, a new genus for the “Adites” maculata (Poujade, 1886) species-group, with descriptions of five new species from northern Indochina and eastern China (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2021)
The new genus Cabardites gen. n. is erected for the Adites maculata (Poujade, 1886) species-group with Asura limbata Wileman, 1911 as the type species. Four new species are described: Cabardites phifa Volynkin & Černý, sp. n. (North Thailand), C. auco Volynkin & Černý, sp. n. (North Vietnam), C. guanyin Volynkin & Černý, sp. n. (East China), C. tiendung Volynkin & Černý, sp. n. (North Vietnam) and C. varanagara Volynkin & Černý, sp. n. (North Thailand). Cabardites pica (Wileman, 1911), stat. & comb. n. is excluded from the synonymy with C. limbata stat. rev. & comb. n. and raised to the species level. Parasiccia fuscipennis Hampson, 1914 is synonymized with C. pica. Parasiccia karenkonis Matsumura, 1930 is excluded from the synonymy with C. maculata (Poujade, 1886), comb. n. and its belonging to the genus Metaemene Hampson (Erebidae, Boletobiinae) proposed by Poole (1989) is confirmed: Metaemene karenkonis (Matsumura, 1930), comb. rev. A new combination is established: Cabardites maculata (Poujade, 1886), comb. n. The lectotypes are designated for Parasiccia maculata var. formosibia Strand, 1917 and Asura limbata Wileman, 1911. Adults, male and female genitalia of all species of the genus are illustrated.